Tweeting democracy: analyzing twitter's role in public participation during the Philippine election 2022 - Tenorio, Christine B.; Daud, Yammie Palao; Lubos, Lalevie Casas (Otoritas : Jurnal Ilmu Pemerintahan, 2024)
This study displays Twitter's relevance in collecting sentiments and evaluating social networks, notably in election processes. This study examines 10,000 tweets on the 2022 Philippine presidential election, gathered during the key week of May 9–13, 2022, to show Twitter's influence in molding the public conversation. The study found the most popular hashtags, including #halalan2022 and #eleksyon2022, highlighting their importance in the digital discussion around the election. A thorough social network study established eight key communities, demonstrating a strong connection among Filipino netizens during election-related debates. Among these, noteworthy people such as @RexelBartolome and @daywreckoning, as well as the news site @ABSCBNEWS, emerged as essential nodes, demonstrating their influence in information dissemination. Sentiment analysis of the tweets revealed a mostly neutral public mood toward the election, with frequent phrases such as "martial law" and "never again" indicating the discourse's underlying themes. This study examines Twitter as a valuable instrument for political analysis and advocates for a more sophisticated method of picking tweets that truly reflect community attitudes. Future studies should look beyond pre-election times to provide a complete picture of online debate, using Twitter's API for easy data gathering and analysis. This study closes a fundamental gap in understanding social media dynamics in the Philippines, providing insights for academic and practical applications in political communication.